Adaptive traits for drought tolerance in red-grained wheat (Triticum aestivum L.) landraces. Issue 4 (2nd October 2021) - Waseem, Muhammad; Mumtaz, Sahar; Hameed, Mansoor; Fatima, Sana; Ahmad, Muhammad Sajid Aqeel; Ahmad, Farooq; Ashraf, Muhammad; Ahmad, Iftikhar
Abstract: Forty-nine accessions were collected from arid and semi-arid areas of Pakistan to explore adaptive components in red-grained wheat ( Triticum aestivum L.). Single-line selections of these accessions were grown on an arid and a control site; that is, Uchkera Farm (UF) and Botanical Garden (BG), Faisalabad. The accessions grown at BG exhibited significantly better biomass and grain yield production than those grown at UF. Accession Ck5 from Chakwal produced the maximum grain yield (17.7 g plant −1 ) at BG and Jm3 (8.1 g plant −1 ) at UF. Among the eight accessions selected for further anatomical studies, Dg2 showed increased yield per plant at UF, which was related to root modifications like increased cortical region thickness, endodermal cell area, vascular region thickness, metaxylem area, and root hair length. Stem modifications included increased vascular bundle area, phloem area and stomatal density, while leaves showed increased cuticle thickness, bulliform cell thickness, trichome density, and length. Increased stomatal density and area were also found. Accession Jm3 showed a decrease in yield at UF. Root modifications in Jm3 included increased epidermal cell area, sclerenchymatous thickness, endodermal cell area, and root hair length. Stem modifications in this accession included increased stem cellular region thickness and sclerenchymatous cell area. Leaves had increased abaxial epidermal cell area, trichome number and length, and abaxial stomatal density. In conclusion, morpho-anatomical characteristics varied greatly in the red-grained wheat accessions at both experimental sites that have potential for incorporation into breeding efforts for drought tolerance in modern wheat cultivars.